The Influence Of The Village Financial System, Government Internal Control System, Transparency, And The Role Of Village Apparatus On Accountability Of Village Financial Management - Selpiy, Jurmaini; Aira, Aras (InJEBA : International Journal of Economics, Business and Accounting, 2024)
This study aims to determine the influence of the village financial system, government internal control system, transparency and the role of village apparatus on the accountability of village financial management in villages in the Kuantan Tengah District, Kuantan Singingi Regency. This type of research is quantitative. The data used are primary data obtained from the distribution of questionnaires. The population of this study is all village officials and BPD members from 20 villages in the Kuantan Tengah sub-district. The sampling technique uses purposive sampling. The data analysis method used is Structural Equation Modeling based on – Partial Least Square (SEM-PLS) with Smart PLS 4 data analysis tool. The results of this research show that the village financial system, government internal control system, transparency and the role of village officials influence management accountability. village finances. The R square test results show that the contribution of all independent variables in explaining the dependent variable is 71.9%, while the other 28.1% is influenced by other factors outside this research.